Analisis Kemampuan Literasi Numerasi Matematis Siswa pada Materi Matriks Ditinjau dari Self-Efficacy - Ambarwati, Estira Dewi; Utin Desy Susiaty; Muhamad Firdaus (Indo-MathEdu Intellectuals Journal, 2023)
The aim of this research is to determine students' mathematical numeracy literacy skills in matrix material in terms of the self-efficacy of class XI IPA 3 SMA Negeri 1 Simpang Hilir, totaling 28 students. Of the 28 students, they will be categorized based on each student's abilities. This research began by providing a self-efficacy questionnaire, a test of numeracy literacy skills, and interviews to categorize students' ability levels. After this, it was continued with analyzing and categorizing based on self-efficacy and level of numeracy literacy skills to determine the research subjects who would be interviewed by selecting 9 subjects. The results of the research concluded that students who have high self-efficacy meet 3 indicators, namely using various kinds of numbers and symbols related to basic mathematics to solve problems in various contexts of daily life, analyzing information displayed in various forms (graphs, tables, sections, diagrams, and so on), and interpret the results of the analysis to predict and make decisions. Students who have moderate self-efficacy meet 2 indicators, namely using various kinds of numbers and symbols related to basic mathematics to solve problems in various contexts of daily life, analyzing information displayed in various forms (graphs, tables, sections, diagrams, etc). Students who have low self-efficacy only meet 1 indicator, namely using a wide variety of numbers and symbols related to basic mathematics to solve problems in various contexts of daily life.